Комплексне моделювання системи автоматичного регулювання частоти та потужності в динамічних режимах роботи ОЕС України - Кириленко, О.В.; Павловський, В.В.; Стелюк, А.О.; Лук'яненко, Л.М. (Технічна електродинаміка, 2012)
The complex model of automatic generation control (AGC) in the integrated power system (IPS) of Ukraine has been proposed. The advantages of the proposed AGC model over existing AGC models have been shown. The modeling results in dynamical operations of IPS of Russia, Ukraine and Belarus in the event of the net power flow set-point readjustment and disconnection of a generating unit are presented.